2006
DOI: 10.1111/j.1365-2567.2006.02433.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐interleukin‐6 monoclonal antibody inhibits autoimmune responses in a murine model of systemic lupus erythematosus

Abstract: SummarySystemic lupus erythematosus (SLE) is an autoimmune disease resulting from dysregulation of the immune system. Interleukin-6 (IL-6) is a multifunctional cytokine produced by macrophages, monocytes and T and B cells. It stimulates B-cell differentiation/maturation, immunoglobulin secretion, and T-cell functions. Elevated levels of IL-6 in serum, urine and renal glomeruli were detected in patients with active SLE and in murine models of SLE. Our study investigated the role of IL-6 in an SLE-like disease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
3
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(105 citation statements)
references
References 28 publications
2
98
3
2
Order By: Relevance
“…Overproduction of IL-6 has been associated with SLE (58) and IL-6 administration exacerbated the lupus disease in NZB/W F 1 mice (59). Conversely, anti-IL-6 mAb inhibited autoimmune responses in this lupus strain (60) and had a beneficial effect on the renal disease by inducing a diminution of anti-dsDNA autoantibody production and a significant reduction of the number of CD21 ϩ CD23 Ϫ MZ B cells, all features that were also present in TLR4-deficient B6 lpr/lpr mice. Similarly, IFN-␥ is involved in the pathogenesis of mouse lupus (61)(62)(63).…”
Section: Discussionmentioning
confidence: 94%
“…Overproduction of IL-6 has been associated with SLE (58) and IL-6 administration exacerbated the lupus disease in NZB/W F 1 mice (59). Conversely, anti-IL-6 mAb inhibited autoimmune responses in this lupus strain (60) and had a beneficial effect on the renal disease by inducing a diminution of anti-dsDNA autoantibody production and a significant reduction of the number of CD21 ϩ CD23 Ϫ MZ B cells, all features that were also present in TLR4-deficient B6 lpr/lpr mice. Similarly, IFN-␥ is involved in the pathogenesis of mouse lupus (61)(62)(63).…”
Section: Discussionmentioning
confidence: 94%
“…These studies emphasize the importance of steady-state levels of IL-6 for responses to infection, as well as the ability of IL-6 to cause severe immunopathology when expressed at high levels. Given the long association between IL-6 and SLE (36,37,(46)(47)(48)(49), it is surprising that there are very few studies that have targeted the IL-6 axis in SLE, and no significant clinical trials using anti-IL-6 (tocilizumab), even though targeting of IL-6 has been shown to be successful in the treatment of autoimmune-prone animals (50)(51)(52). This is particularly surprising given that therapies targeting IL-6 have been shown to be very effective in the treatment of other autoimmune diseases such as rheumatoid arthritis (53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…32 Application of anti-IL-6R as well as anti-IL-6 antibodies were subsequently shown to ameliorate disease by two independent groups. 33,34 Mechanistically, the deleterious effects of IL-6 were largely ascribed to production of pathogenic antibodies. Some authors also suspected IL-6 effects on T-cell activation; however, this was not addressed any further and effects on Th17 responses have not yet been studied.…”
mentioning
confidence: 99%